Functional implications of strength training on older adults: a literature review (2017)
Aging is a set of processes, inherent of living beings, of which induce loss of capacity to adapt into the environment by decreased functionality. It is associated to a declivity of the functions of the musculoskeletal and neuromuscular systems converging in degrowth of all expressions of muscular strength, including maximum, power and the reaction time. The functional capacity makes reference to a multidimensional quality, however, for the particular aspect of physical functioning, it is considered as the physiologic capacity to perform activities of daily living safely and independently, without provoking exhaustion. To fight the phenomena that promote the continued loss of functional capacity, they require strategies that promote benefits in musculoskeletal and neuromuscular systems, especially if you manage to decrease the speed of deterioration, benefit the quality of life, functional independence and influence increased life expectancies. Both older men and women, the different modalities of strength training can constitute a proper strategy to combat these effects. The purpose of this review article was to systematize the alterations of skeletal muscle during aging and the derivatives muscular adaptations of the different strength training in older adults systems, based on the most conspicuous and relevant scientific literature. The synthesis of results justifies the importance of the application of strength training to avoid sarcopenia, dynapenia and optimize the functional capacity in older adults. Is paramount the knowledge on muscle characteristics (morphological and neuromuscular) necessary in the implementation of the different modalities of training. The adaptations provided by the reagent system training, showing greater functional benefits for older adults, collated with traditional training modalities and the power training.